Polyoxide composite corundum-based heat-absorbing ceramic and preparation method thereof

By using multi-oxide composite corundum heat-absorbing ceramics, using raw materials such as bauxite and introducing admixtures, the problems of low absorption rate and reduced high-temperature performance of existing heat-absorbing ceramics are solved, and efficient absorption and good high-temperature resistance are achieved. .

CN119430887AActive Publication Date: 2025-02-14CHINA HUBEI LONGZHONG LABORATORY +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411878129.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-14
Estimated Expiration
2044-12-19

AI Technical Summary

Technical Problem

The existing heat-absorbing ceramics prepared with bauxite as raw material have problems such as low absorption rate and reduced performance during service at high temperatures.

Method used

Use multioxide composite corundum heat-absorbent ceramics, including bauxite, iron oxide, titanium oxide, copper oxide and admixtures (such as lanthanide metal oxides, transition metal oxides and post-transition metal oxides) as raw materials, and Prepared by specific mixing, granulation and sintering processes.

Benefits of technology

The absorption rate and flexural strength of the heat-absorbing ceramic are improved, and have excellent high-temperature resistance. After 100 hours of high-temperature service, the absorption rate can still reach 91.7~92.5%, and the flexural strength remains 105.99~121.69 MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430887A_ABST
    Figure CN119430887A_ABST
Patent Text Reader

Abstract

The invention relates to a multi-oxide composite corundum-based heat-absorbing ceramic and a preparation method thereof, the multi-oxide composite corundum-based heat-absorbing ceramic comprises the following raw materials by mass: 80-95 parts of bauxite, 8-10 parts of iron oxide, 0.4-1 part of titanium oxide, 6-8 parts of copper oxide, and 1-5 parts of an additive; the additive comprises at least one of lanthanide metal oxide, transition metal oxide and late transition metal oxide. The bauxite, the iron oxide, the titanium oxide, the copper oxide and the additive are used as raw materials, and the used raw material bauxite is low in price and accounts for 75% or above, so that the cost is effectively reduced; through introduction of the additive and cooperation of ferric oxide, titanium oxide and copper oxide, the formed heat-absorbing ceramic is high in absorptivity and good in breaking strength; the high-temperature resistance is excellent, and the preparation process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar thermal power generation heat-absorbing materials, and in particular to a multi-oxide composite corundum-based heat-absorbing ceramic and a preparation method thereof. Background Art

[0002] Large-scale utilization of solar energy is an important way to alleviate the shortage of fossil fuels. Tower solar thermal power generation has the characteristics of high concentration multiples and high power generation efficiency, and is considered to be the most commercially promising and most potential solar energy development and utilization technology. As the core component of tower solar thermal power generation, receiver materials are required to have high absorption rate and excellent high-temperature performance.

[0003] At present, the widely used receiving materials are silicon carbide and its composite materials with aluminum nitride. For example, Chinese patent CN111269015A discloses a densified mullite-corundum-SiC composite heat storage ceramic material for solar thermal power generation and its preparation method, providing a ceramic heat storage material with mullite / corundum / SiC as the main crystal phase. The prepared ceramic material has high density and mechanical properties, and the volume density and flexural strength can reach 2.30g·cm -3 and 77.05MPa. Chinese patent CN111253158A discloses a solar thermal power generation absorption / storage integrated corundum / SiC ceramic material and its preparation method, providing a ceramic heat absorption material with corundum / SiC as the main crystal phase, with an absorption rate of up to 91% and a flexural strength of 76MPa to 85MPa. However, they have problems such as poor oxidation resistance, high cost of synthetic materials or complex process.

[0004] Oxide-based ceramic materials such as alumina have attracted more and more attention due to their high thermal oxidation resistance, low processing cost and excellent mechanical properties. For example, Chinese patent CN107140964A discloses a solar heat-absorbing ceramic material with high resistance to high-temperature oxidation and its preparation method, providing a solar heat-absorbing ceramic material with high resistance to high-temperature oxidation, which increases the content of the three main components of magnesium oxide, sodium silicate and alumina, and has a significant effect on improving the material's resistance to high-temperature oxidation. However, the cost of using alumina directly as a raw material is relatively high, and the heat-absorbing ceramics prepared by replacing it with aluminum-containing raw materials, such as bauxite, have problems such as low absorption rate and obvious performance degradation when in high-temperature service. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a multi-oxide composite corundum-based heat-absorbing ceramic and a preparation method thereof, and solve the technical problems in the prior art that heat-absorbing ceramics prepared with bauxite as raw material have low absorption rate and decreased performance when in high-temperature service.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a multi-oxide composite corundum-based endothermic ceramic, which comprises the following raw materials, by mass: 80 to 95 parts of bauxite, 8 to 10 parts of iron oxide, 0.4 to 1 part of titanium oxide, 6 to 8 parts of copper oxide, and 1 to 5 parts of an additive; the additive comprises at least one of a lanthanide metal oxide, a transition metal oxide, and a post-transition metal oxide.

[0007] In a second aspect, the present invention provides a method for preparing a multi-oxide composite corundum-based endothermic ceramic, comprising the following steps: S1, uniformly mixing bauxite, iron oxide, titanium oxide, copper oxide and an additive in proportion to obtain a mixed powder; S2, adding an organic binder to the mixed powder for granulation, pressing and molding after aging to obtain a green body; S3, drying and sintering the green body to obtain a multi-oxide composite corundum-based endothermic ceramic.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The multi-oxide composite corundum-based endothermic ceramic of the present invention uses bauxite, iron oxide, titanium oxide, copper oxide and additives as raw materials, and the raw material bauxite used is cheap, but its proportion is more than 75%, thereby effectively reducing the cost; by introducing additives and in the combination of iron oxide, titanium oxide and copper oxide, the endothermic ceramic formed has high absorption rate and good flexural strength; excellent high temperature resistance, after 100 hours of high temperature service (1000°C), the absorption rate can still reach 91.7-92.5%, and the flexural strength is maintained at 105.99-121.69 MPa; and the preparation process is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 is the XRD diagram of the multi-oxide composite corundum-based endothermic ceramic in Example 3 of the present invention; Figure 2 This is a SEM image of the multi-oxide composite corundum-based endothermic ceramic in Example 3 of the present invention. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] The present invention provides a low-cost, long-life multi-oxide composite corundum-based heat-absorbing ceramic and a preparation method thereof, which are used to solve the technical problems that the existing heat-absorbing ceramics prepared with bauxite as raw material have low absorption rate and reduced performance when in high-temperature service.

[0012] In a first aspect, the present invention provides a multi-oxide composite corundum-based endothermic ceramic, which comprises the following raw materials, by mass: 80 to 95 parts of bauxite, 8 to 10 parts of iron oxide, 0.4 to 1 part of titanium oxide, 6 to 8 parts of copper oxide, and 1 to 5 parts of an additive; the additive comprises at least one of a lanthanide metal oxide, a transition metal oxide, and a post-transition metal oxide.

[0013] Preferably, the additive includes lanthanum oxide, praseodymium oxide, cobalt oxide or tin oxide.

[0014] Preferably, the components of bauxite include, by mass percentage: SiO2: 10-11wt%; Al2O3: 80-81wt%; CaO: 0.1-1wt%; Fe2O3: 1-2wt%; TiO2: 3-4wt%; MgO: 0.1-1wt%; K2O: 0.1-1wt%; Na2O: 0.01-0.1wt%; and 1-2% loss on ignition.

[0015] Preferably, the main crystalline phase of the heat-absorbing ceramic includes a corundum phase, and the secondary crystalline phases include iron titanate, spinel and quartz phases; the spinel includes an iron-aluminum spinel phase (with additives of lanthanum oxide, praseodymium oxide and tin oxide) or a copper-cobalt spinel phase (with additive of cobalt oxide).

[0016] In a second aspect, the present invention provides a method for preparing a multi-oxide composite corundum-based endothermic ceramic, comprising the following steps: S1, mixing bauxite, iron oxide, titanium oxide, copper oxide and additives in proportion to obtain a mixed powder; S2, adding an organic binder to the mixed powder to granulate, and pressing and molding after aging to obtain a green body; S3, the green body is dried and then sintered to obtain a multi-oxide composite corundum-based endothermic ceramic.

[0017] Preferably, in step S1, bauxite, iron oxide, titanium oxide, copper oxide and additives are mixed uniformly by ball milling.

[0018] More preferably, the powder is ball-milled to a particle size of ≥250 mesh.

[0019] Preferably, in step S2, the amount of organic binder added is 5-9% of the mass of the mixed powder; the organic binder is a polyvinyl alcohol aqueous solution with a mass concentration of 4-6%.

[0020] Preferably, in step S3, the aging conditions include: aging at 25-30° C. for 24-48 hours.

[0021] Preferably, in step S3, the pressing pressure is 30-50 kN.

[0022] Preferably, in step S4, drying is performed at 80-90° C. for 24-48 hours.

[0023] Preferably, in step S4, the sintering conditions include: heating to 1320° C. to 1400° C. and keeping the temperature for 1 to 2 hours.

[0024] Preferably, in step S4, the heating rate of sintering is 3-5°C / min.

[0025] The present invention is further described in detail by specific embodiments. The components of the bauxite used include, by mass percentage, SiO2: 10.72wt%; Al2O3: 80.56wt%; CaO: 0.87wt%; Fe2O3: 1.5wt%; TiO2: 3.86wt%; MgO: 0.3wt%; K2O: 0.45wt%; Na2O: 0.06wt%; and 1.68% ignition loss.

[0026] In the test, according to the Archimedes principle, the volume density (D) of the sample was determined by the drainage method: specifically, the sample was immersed in a vacuum environment for 30 minutes using the TXY digital ceramic water absorption tester of Xiangtan Xiangyi Instrument Co., Ltd. to make the sample reach a saturated state of water absorption, and the saturated sample was immersed in water, and the sample mass M2 (suspended weight) was measured using a hydrometer; the sample was taken out of the immersion liquid, and the liquid droplets on the surface of the saturated sample were wiped off with a saturated water-absorbent towel, and then the sample mass M3 (wet weight) was measured. The specific calculation formula is as follows: (1) Where: D is the volume density, g / cm 3 ; D1 is the density of the immersion liquid, g / cm 3 When measuring water absorption, the immersion liquid used is water, and its density is 1 g / cm 3 .

[0027] The three-point bending method (refer to national standard GB5101-2003) was used to test the flexural strength of the sample using an electronic universal testing machine (model RGM-4100) with a loading speed of 0.5 mm / min. The flexural strength of the sample was obtained by the following calculation formula (2): (2) Where: b - flexural strength of the sample, MPa; P - load when the sample breaks, N; L - distance between the blades used to support the sample, mm; K - lever arm ratio, the value of this model of instrument is 1; B - width of the sample at the fracture position, mm; H - thickness of the sample at the fracture position, mm.

[0028] The reflectance of the sample was tested using an ultraviolet-visible-near infrared spectrophotometer (model: UV-3600), and the solar light absorption rate was calculated using the following formula (3): (3) Where: αs-solar absorption rate of the sample, %; λ -wavelength, μm; ρ s (λ)-reflectivity, %; E s (λ) -solar radiation intensity, W.

[0029] The high-temperature service test process is as follows: after the sintered sample is placed in a durable electric furnace, the resistance furnace is heated to 1000°C at a rate of 5°C / min, and after being kept at this temperature for 10 hours, the sample is cooled to room temperature with the furnace, and the first durability process is completed after the sample is taken out. According to the above process, the sample is kept at this temperature for a total of 100 hours, and its high-temperature stability is characterized by the changes in the solar light absorption rate and flexural strength of the sample. The flexural strength is tested, which is characterized by the strength loss rate, which can be obtained by formula (4): (4) Where: σ0-flexural strength of the sample after 0 times of endurance (MPa); σ n -Flexural strength of the sample after endurance n times (MPa), n=1, 2, 3, 4, 5, 6, 7, 8, 9, 10; S σ -Strength loss rate (%).

[0030] Example 1 A method for preparing a multi-oxide composite corundum-based endothermic ceramic comprises the following steps: S1, by weight, 90 parts of bauxite, 9.5 parts of iron oxide, 0.5 parts of titanium oxide, 7 parts of copper oxide and 3 parts of an additive are placed in a ball mill and milled to obtain a mixed powder of 250 mesh; wherein the additive is lanthanum oxide; S2, adding an organic binder (5% PVA aqueous solution) accounting for 7wt% of the mixed powder mass to the mixed powder for granulation; storing the granulated raw materials in a sealed container and aging at 25°C for 24h; and then pressing and molding at a pressure of 40kN to obtain a green body; S3, placing the green body in a constant temperature drying oven and drying it at 90°C for 24 hours; placing the dried green body in a high temperature electric furnace, heating it to 1360°C at a heating rate of 3-5°C / min and sintering it for 2 hours to obtain a multi-oxide composite corundum-based endothermic ceramic.

[0031] The test results show that the low-cost and long-life multi-oxide composite corundum-based endothermic ceramic sample prepared in Example 1 of the present invention has an absorption rate of 93.4%, a flexural strength of 123.78 MPa, and a volume density of 3.65 g / cm 3After 100 hours of high temperature service (1000℃), the absorption rate of the sample is 92.0%, which is 1.4% lower than before high temperature service. After 100 hours of high temperature service (1000℃), the flexural strength of the sample is 107.37MPa, which is 13.2% lower than before high temperature service.

[0032] Example 2 The only difference from Example 1 is that the additive in the raw material is adjusted to praseodymium oxide, and the other steps and conditions are the same as those in Example 1.

[0033] The test results show that the low-cost and long-life multi-oxide composite corundum-based endothermic ceramic sample prepared in Example 2 of the present invention has an absorption rate of 93.1%, a flexural strength of 113.3 MPa, and a volume density of 3.63 g / cm 3 After 100 hours of high temperature service (1000℃), the absorption rate of the sample is 91.7%, which is 1.4% lower than before high temperature service. After 100 hours of high temperature service (1000℃), the flexural strength of the sample is 105.99MPa, which is 6.4% lower than before high temperature service.

[0034] Example 3 The only difference from Example 1 is that the additive in the raw material is adjusted to cobalt oxide, and the other steps and conditions are the same as those in Example 1.

[0035] The test results show that the low-cost and long-life multi-oxide composite corundum-based endothermic ceramic sample prepared in Example 3 of the present invention has an absorption rate of 93.1%, a flexural strength of 113.09 MPa, and a volume density of 3.58 g / cm 3 After 100 hours of high temperature service (1000℃), the absorption rate of the sample is 92.5%, which is 0.6% lower than before high temperature service. After 100 hours of high temperature service (1000℃), the flexural strength of the sample is 121.69MPa, which is 7.6% higher than before high temperature service.

[0036] Example 4 The only difference from Example 1 is that the additive in the raw material is adjusted to tin oxide, and the other steps and conditions are the same as those in Example 1.

[0037] The test results show that the low-cost and long-life multi-oxide composite corundum-based endothermic ceramic sample prepared in Example 4 of the present invention has an absorption rate of 93.2%, a flexural strength of 132.44 MPa, and a volume density of 3.66 g / cm 3 After 100 hours of high temperature service (1000℃), the absorption rate of the sample is 92.4%, which is 0.8% lower than before high temperature service. After 100 hours of high temperature service (1000℃), the flexural strength of the sample is 117.65MPa, which is 11.1% lower than before high temperature service.

[0038] Comparative Example 1 The only difference from Example 1 is that the admixture is removed from the raw materials, and the other steps and conditions are the same as those in Example 1.

[0039] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 1 had an absorption rate of 92.1% and a flexural strength of 106.02 MPa.

[0040] Comparative Example 2 The only difference from Example 1 is that the number of admixtures in the raw material is adjusted to 1 part, and the other steps and conditions are the same as those in Example 1.

[0041] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 2 had an absorption rate of 93% and a flexural strength of 122.38 MPa.

[0042] Comparative Example 3 The only difference from Example 1 is that the number of admixtures in the raw material is adjusted to 5 parts, and the other steps and conditions are the same as those in Example 1.

[0043] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 3 had an absorption rate of 93.1% and a flexural strength of 129.63 MPa.

[0044] Comparative Example 4 The only difference from Example 2 is that the number of admixtures in the raw material is adjusted to 1 part, and the other steps and conditions are the same as those in Example 2.

[0045] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 4 had an absorption rate of 93% and a flexural strength of 100.16 MPa.

[0046] Comparative Example 5 The only difference from Example 2 is that the number of admixtures in the raw material is adjusted to 5 parts, and the other steps and conditions are the same as those in Example 2.

[0047] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 5 had an absorption rate of 92.5% and a flexural strength of 118.64 MPa.

[0048] Comparative Example 6 The only difference from Example 3 is that the number of admixtures in the raw material is adjusted to 1 part, and the other steps and conditions are the same as those in Example 3.

[0049] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 6 had an absorption rate of 91.5% and a flexural strength of 112.44 MPa.

[0050] Comparative Example 7 The only difference from Example 3 is that the number of admixtures in the raw material is adjusted to 5 parts, and the other steps and conditions are the same as those in Example 3.

[0051] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 7 had an absorption rate of 92.3% and a flexural strength of 108.44 MPa.

[0052] Comparative Example 8 The only difference from Example 4 is that the number of admixtures in the raw material is adjusted to 1 part, and the other steps and conditions are the same as those in Example 4.

[0053] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 8 had an absorption rate of 92.1% and a flexural strength of 122.42 MPa.

[0054] Comparative Example 9 The only difference from Example 4 is that the number of admixtures in the raw material is adjusted to 5 parts, and the other steps and conditions are the same as those in Example 4.

[0055] The test found that the alumina-based heat-absorbing ceramic sample prepared in Comparative Example 9 had an absorption rate of 92.3% and a flexural strength of 136.62 MPa.

[0056] In tower solar thermal power generation applications, the absorptivity of corundum-based heat-absorbing ceramics directly affects the light-to-heat conversion efficiency of the thermal power generation system, and absorptivity is a key performance of heat-absorbing materials.

[0057] By setting three different addition amount gradients for the four additives, experiments of Examples 1 to 4 and Comparative Examples 2 to 9 were conducted to explore the optimal addition amount to improve the absorption rate. The test results show that the absorption rate of 3 parts of each additive (Examples 1 to 4) is higher than that of 1 part and 5 parts (Comparative Examples 2 to 9). For example, the absorption rate of Comparative Example 8 is 92.1, the absorption rate of Comparative Example 9 is 92.3, and the absorption rate of Example 4 is 93.2. The absorption rate of Example 4 is much higher than that of Comparative Examples 8 and Comparative Example 9, and each example is much higher than the absorption rate of the sample without adding additives.

[0058] When heat-absorbing ceramics are used in a tower solar thermal power generation system, in addition to having a high solar light absorption rate, they should also have excellent high temperature resistance. Therefore, Examples 1 to 4 were selected for high temperature service experiments. The performance of the heat-absorbing ceramics obtained in the above examples was statistically analyzed, and the results are shown in Table 1 below.

[0059] Table 1 Properties of heat-absorbing ceramics obtained in various embodiments

[0060] By comparing Examples 1-4 with Comparative Example 1, it can be seen that the introduction of the admixture improves the absorptivity and flexural strength of the corundum-based endothermic ceramic. And by comparing Examples 1-4, it can be seen that Example 3 has excellent high-temperature service performance. After 100 hours of high-temperature service (1000°C), the absorptivity is 92.5% (only decreased by 0.6%), and the flexural strength is 121.69MPa (increased by 7.6%). Therefore, the performance of the cobalt oxide admixture used in the present invention is the best.

[0061] Figure 1 The XRD diagram of the multi-oxide composite corundum-based endothermic ceramic provided in Example 3 of the present invention; Figure 1 It can be seen that the main crystalline phase of the multi-oxide composite corundum-based endothermic ceramic sample prepared in the embodiment of the present invention is the corundum phase, and the secondary crystalline phases are iron titanate, copper-cobalt spinel and quartz phases.

[0062] Figure 2 This is a SEM image of the multi-oxide composite corundum-based endothermic ceramic provided in Example 3 of the present invention; Figure 2 It can be seen that the multi-oxide composite corundum-based endothermic ceramic sample prepared in the embodiment of the present invention has aggregated spherical small particles distributed in it, which are copper-cobalt spinel grains. 3+ , in O 2- In the tetrahedral coordination field, Co 3+ The electronic energy level makes the transition absorption band generally appear in the near-ultraviolet and visible light regions. In addition, the introduction of Co2O3 causes more defects inside the sample, forming impurity energy levels, thereby reducing the bandgap width, reducing the energy required for electrons to transition from the valence band to the conduction band, broadening the light absorption range of the sample, and improving the solar light absorption rate of the sample. During the high-temperature service of the sample, thermal energy drives copper ions into the lattice, and the sample forms more copper-cobalt spinel under the action of Co2O3. The formation of copper-cobalt spinel makes Co 3+ The d orbital of Co is split into orbitals of unequal energy in the tetrahedral coordination field. 3+ The electronic energy level transition still exists, so the absorption rate of the sample does not show a significant decrease after high-temperature service.

[0063] The multi-oxide composite corundum-based endothermic ceramic of the present invention uses bauxite, iron oxide, titanium oxide, copper oxide and additives as raw materials, and the proportion of bauxite is more than 75%, which effectively reduces the cost; by introducing additives, and in the combination of iron oxide, titanium oxide and copper oxide, the absorption rate (93.1-93.4%) and flexural strength (113.09-132.44 MPa) of the obtained corundum-based endothermic ceramic are effectively improved; and the obtained multi-oxide composite corundum-based endothermic ceramic has excellent high temperature resistance, and the absorption rate can still reach 91.7-92.5% after 100h of high temperature service (1000°C), and the flexural strength is 105.99-121.69 MPa; therefore, the raw materials used in the present invention are low in price, the obtained material has high absorption rate, excellent high temperature resistance and good flexural strength, and is a low-cost and long-life endothermic ceramic, and the preparation process is simple.

[0064] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A multi-oxide composite corundum-based endothermic ceramic, characterized in that: The raw materials include, by weight: 80-95 parts of bauxite, 8-10 parts of iron oxide, 0.4-1 parts of titanium oxide, 6-8 parts of copper oxide, and 1-5 parts of additives; The additive includes at least one of lanthanide metal oxides, transition metal oxides and post-transition metal oxides.

2. The multi-oxide composite corundum-based endothermic ceramic according to claim 1, characterized in that: The additive includes lanthanum oxide, praseodymium oxide, cobalt oxide or tin oxide.

3. The multi-oxide composite corundum-based endothermic ceramic according to claim 1, characterized in that: The components of the bauxite include, by mass percentage: SiO2: 10-11%, Al2O3: 80-81%, CaO: 0.1-1%, Fe2O3: 1-2%, TiO2: 3-4%, MgO: 0.1-1%, K2O: 0.1-1%, Na2O: 0.01-0.1%, and 1-2% loss on ignition.

4. The multi-oxide composite corundum-based endothermic ceramic according to claim 1, characterized in that: The main crystal phase of the multi-oxide composite corundum-based heat-absorbing ceramic includes a corundum phase, and the secondary crystal phase includes iron titanate, spinel and quartz phases.

5. The method for preparing the multi-oxide composite corundum-based endothermic ceramic according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing bauxite, iron oxide, titanium oxide, copper oxide and additives in proportion to obtain a mixed powder; S2, adding an organic binder to the mixed powder to granulate, and pressing and molding after aging to obtain a green body; S3, the green body is dried and then sintered to obtain the multi-oxide composite corundum-based endothermic ceramic.

6. The method for preparing the multi-oxide composite corundum-based endothermic ceramic according to claim 5, characterized in that: In step S1, bauxite, iron oxide, titanium oxide, copper oxide and additives are mixed uniformly by ball milling.

7. The method for preparing the multi-oxide composite corundum-based endothermic ceramic according to claim 5, characterized in that: In step S2, the amount of the organic binder added is 5-9% of the mass of the mixed powder; the organic binder is a polyvinyl alcohol aqueous solution with a mass concentration of 4-6%.

8. The method for preparing the multi-oxide composite corundum-based endothermic ceramic according to claim 5, characterized in that: In step S3, the aging conditions include: aging at 25-30° C. for 24-48 hours; The pressing pressure is 30 to 50 kN.

9. The method for preparing the multi-oxide composite corundum-based endothermic ceramic according to claim 5, characterized in that: In step S4, drying is performed at 80 to 90° C. for 24 to 48 hours.

10. The method for preparing the multi-oxide composite corundum-based endothermic ceramic according to claim 5, characterized in that: In step S4, the sintering conditions include: heating to 1320°C to 1400°C and keeping the temperature for 1 to 2 hours; The heating rate of sintering is 3-5°C / min.

Citation Information

Patent Citations

  • Solar heat absorption ceramic material with high high-temperature oxidation resistance and preparation method thereof

    CN107140964A

  • Solar thermal power generation and heat absorption / storage integrated corundum / SiC ceramic material and preparation method thereof

    CN111253158A

  • Compact mullite-corundum-SiC complex phase heat storage ceramic material for solar thermal power generation, and preparation method thereof

    CN111269015A

  • Phase change thermal storage material

    CN109628068A

  • Full spectrum photothermal conversion heat storage material and preparation method thereof

    CN109735310A